Dynamic Success Dynamics of SMEs in Digital Transformation: Analysis of Social and Psychological Factors - Manafe, Mesri Welhelmina Nisriani (ADMAN: Journal of Contemporary Administration and Management, 2024)
The advancement of information and communication technology has transformed the way business is conducted. Small and Medium Enterprises (SMEs) often face challenges in adopting these changes, including difficulties in integrating digital technology into their operations. This research aims to understand the dynamics of the successful adaptation of Micro, Small, and Medium Enterprises (SMEs) to digital transformation, employing an analysis approach that considers social and psychological factors. The study utilizes a qualitative literature review method, focusing on data from Google Scholar within the range of 2009-2023. The study's findings indicate that SMEs, when confronting digital transformation, can draw several important conclusions. Firstly, it is crucial to build strong relationships with customers, business partners, and the community through social media and business networks to garner necessary support. Secondly, SME owners need to cultivate an adaptive and innovative mindset, along with the ability to take risks and resilience in facing failures. Training and psychological support can help overcome resistance to change. Thirdly, effective management is key to handling digital transformation, with SME owners requiring leadership skills, strategic planning abilities, and expertise in efficiently managing human resources. Managerial training can enhance the leadership capabilities of SME owners.